The role of platelets in the blood-brain barrier during brain pathology - Lv, Weifeng; Jiang, Xiaofan; Zhang, Yanyu (Frontiers in Cellular Neuroscience, 2024)
Platelets play critical roles in maintaining hemostasis. The blood brain barrier (BBB), a significant physical and metabolic barrier, helps maintain physiological stability by limiting transportations between the blood and neural tissues. When the brain undergoes inflammation, tumor, trauma, or bleeding, the platelet responses to help with maintaining BBB homeostasis. In the traditional point of view, activated platelets aggregate to form thrombi which cover the gaps of the blood vessels to protect BBB. However, increasing evidences indicate that platelets may harm BBB by enhancing vascular permeability. Hereby, we reviewed recently published articles with a special focus on the platelet-mediated damage of BBB. Factors released by platelets can induce BBB permeability, which involve platelet-activating factors (PAF), P-selectin, ADP, platelet-derived growth factors (PDGF) superfamily proteins, especially PDGF-AA and PDGF-CC, etc. Platelets can also secrete Amyloid-β (Aβ), which triggers neuroinflammation and downregulates the expression of tight junction molecules such as claudin-5 to damage BBB. Additionally, platelets can form aggregates with neuthrophils to release reactive oxygen species (ROS), which can destroy the DNA, proteins, and lipids of endothelial cells (ECs). Moreover, platelets participate in neuroinflammation to affect BBB. Conversely, some of the platelet released factors such as PDGF-BB, protects BBB. In summary, platelets play dual roles in BBB integrity and the related mechanisms are reviewed.